Effect of Career, Employee Engagement, and Compensation of Behavior Organisational Citizenship in PT. Wika Intinusa Surabaya - Cakrawardani, Dhitanayu; Putra, Bayu Airlangga; Arif, Mochamad (Yayasan Ahmar Cendekia Indonesia, 2020)
This study discusses how career influence, employee involvement, and compensation towards organizational Citizenship Behavior in PT Wika Intinusa Surabaya. This study aims to determine the effect of career, employee involvement, compensation on organizational Citizenship Behavior. The sampling technique in this study is to use the census method. Respondents in this study were 50 active employees in the city of Surabaya. The data analysis method uses multiple linear regression test, with SPSS v.1.8 software as an analysis tool. The results of this study indicate that the variable Career and variable compensation partially affects the Organizational Citizenship behavior, but in Variable Employee Engagement (Employee Engagement) less influential partially on Organizational Citizenship Behavior.